Cap polyposis treated with laparoscopic-assisted total proctocolectomy and ileal J-pouch anal anastomosis: a case report - Tomohiro Minagawa; Hiroki Ikeuchi; Kurando Kusunoki; Ryuichi Kuwahara; Yuki Horio; Takako Kihara; Seiichi Hirota; Motoi Uchino (Surgical Case Reports, 2021)
Abstract Background Cap polyposis (CP) is extremely rare in Japan, and there is no established cure. We report a case in which CP was improved by surgical treatment. Case presentation A 48-year-old man was investigated at a local hospital because of diarrhea and bloody stools in 2018. The patient was treated with metronidazole for suspected amoebic dysentery, but his symptoms did not improve. Subsequent close examination revealed possible CP, but treatment with 5-aminosalicylic acid and a steroid enema had no effect. The patient was then referred to our hospital. The bloody stools, diarrhea, and abdominal pain worsened despite medical treatment, so laparoscopic-assisted total proctocolectomy and ileal J-pouch anal anastomosis with ileostomy were performed. CP has no known cause or established treatment, but Helicobacter pylori (HP) infection has been reported in many CP cases in Japan, and HP eradication is often successful. This patient was HP-negative and did not improve with antimicrobial treatment, but the symptoms improved after surgery. Conclusions Even after surgery, CP recurrence reportedly occurs within a short period in many cases. However, our patient has had no signs of CP recurrence during 1 year of follow-up.